Peripheral vs. Central Sex Steroid Hormones in Experimental Parkinson’s Disease - McArthur, Simon; Gillies, Glenda E. (Frontiers in Endocrinology, 2011)
The nigrostriatal dopaminergic (NSDA) pathway degenerates in Parkinson’s disease (PD), which occurs with approximately twice the incidence in men than women. Studies of the influence of systemic estrogens in females suggest sex hormones contribute to these differences. In this review we analyse the evidence revealing great complexity in the response of the healthy and injured NSDA system to hormonal influences, and emphasize the importance of centrally generated estrogens. At physiological levels, circulating estrogen (in females) or estrogen precursors (testosterone in males, aromatised to estrogen centrally) have negligible effects on dopaminergic neurone survival in experimental PD, but can modify striatal dopamine levels via actions on the activity or adaptive responses of surviving cells. However, these effects are sexually dimorphic. In females, estradiol promotes adaptive responses in the partially injured NSDA pathway, preserving striatal dopamine, whereas in males gonadal steroids and exogenous estradiol have a negligible or even suppressive effect, effectively exacerbating dopamine loss. On balance, the different effects of gonadal factors in males and females contribute to sex differences in experimental PD. Fundamental sex differences in brain organization, including the sexually dimorphic networks regulating NSDA activity are likely to underpin these responses. In contrast, estrogen generated locally appears to preserve striatal dopamine in both sexes. The available data therefore highlight the need to understand the biological basis of sex-specific responses of the NSDA system to peripheral hormones, so as to realise the potential for sex-specific, hormone-based therapies in PD. Furthermore, they suggest that targeting central steroid generation could be equally effective in preserving striatal dopamine in both sexes. Clarification of the relative roles of peripheral and central sex steroid hormones is thus an important challenge for future studies.